A bibliography of the Athapaskan languages - Parr, Richard T. (Book collections on Project MUSE., 1974)
Approximately 5000 entries on the linguistics, anthropology, archaeology, folklore and ethnomusicology of the Athapaskan Indian languages. Covers published materials, theses, dissertations, and archive holdings.